2021
DOI: 10.1038/s12276-021-00630-x
|View full text |Cite
|
Sign up to set email alerts
|

IL-30† (IL-27A): a familiar stranger in immunity, inflammation, and cancer

Abstract: Over the years, interleukin (IL)-27 has received much attention because of its highly divergent, sometimes even opposing, functions in immunity. IL-30, the p28 subunit that forms IL-27 together with Ebi3 and is also known as IL-27p28 or IL-27A, has been considered a surrogate to represent IL-27. However, it was later discovered that IL-30 can form complexes with other protein subunits, potentially leading to overlapping or discrete functions. Furthermore, there is emerging evidence that IL-30 itself may perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 104 publications
1
13
0
Order By: Relevance
“…In this study, we found that the administration of AAV-mIL-30 decreased the activation and IFN-γ production of CD4 + T cells in autoimmune cholangitis. This result is similar to that of previous studies where the administration of IL-30-encoding plasmids decreases the intrinsic ability of CD4 + T cells to produce IFN-γ and where IL-30 conditional knockout mice produce extremely high levels of IFN-γ when injected with ConA [20,21]. However, the immunosuppressive function of IL-30 has been reported in autoimmune diseases such as experimental autoimmune encephalomyelitis and experimental autoimmune uveitis [22,23], though not in liver autoimmune diseases.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that the administration of AAV-mIL-30 decreased the activation and IFN-γ production of CD4 + T cells in autoimmune cholangitis. This result is similar to that of previous studies where the administration of IL-30-encoding plasmids decreases the intrinsic ability of CD4 + T cells to produce IFN-γ and where IL-30 conditional knockout mice produce extremely high levels of IFN-γ when injected with ConA [20,21]. However, the immunosuppressive function of IL-30 has been reported in autoimmune diseases such as experimental autoimmune encephalomyelitis and experimental autoimmune uveitis [22,23], though not in liver autoimmune diseases.…”
Section: Discussionsupporting
confidence: 90%
“…The emergence of IL-27p28, as either a standalone cytokine subunit (that has been labeled IL-30) or one that can pair with soluble receptors other than EBI3 (and create alternative signaling complexes), has drastically expanded the range of immunomodulatory functions for IL-27-related proteins and their expanded roles in physiology and disease ( Min et al., 2021 ). The structural models at high resolution we present here for mouse and human IL-27p28 (IL-30) will undoubtedly help to produce redesigned p28 monomers that could clarify IL-30 biology and its pairing with other receptor subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, another chaperonelike activity of EBI3 was reported for formation of IL-27 (30,31). In mice, p28, also designated as IL-30, is secreted and exerts immunoregulatory roles (41), while human p28 is not autonomously secreted due to the difference in one amino acid residue cysteine that is necessary for disulfide bond formation (30). Without EBI3 human p28 is retained and becomes degraded by the ER quality control machinery, whereas the presence of EBI3 facilitates the proper protein folding, leading to efficient secretion of human p28 and formation of IL-27 heterodimer.…”
Section: Ebi3 Facilitates the Proper Protein Folding Of P28 To Form Il-27mentioning
confidence: 99%